The Absent Minority in Welfare Planning: Entitling or Overburdening Citizens with Responsibility? - Perttola, Laura; Pernaa, Hanna-Kaisa (Socialiniai tyrimai, 2016)
In Finnish health care and social welfare legislation, a shift towards strengthening the individual’s right to participate has been significant during the past two decades. While the traditional presumption of citizen involvement and developing of deliberative democracy lies on normality and social activism, it is becomingapparent that the substantial amount or Finnish social and healthcare expenditure is used by one tenth of citizens who do not fit into this category and can be considered as large-scale consumers of the services. We refer to this group, identified by high service consumption and low participation, as the absent minority. In this paper, we illuminate the legislative and participative possibilities of involving and acknowledging this group in communal welfare service development.
Keywords: deliberative democracy; minority absence; welfare planning; social rights